FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN WISATAWAN INDIA BERKUNJUNG KE BALI - Sunu Dwi Aldrianto, Yohanes; Sendra, I Made; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2019)
Bali has been known for its natural beauty, the friendliness of its residents, and the diversity of its customs. Existing tourist attractions in Bali have a diversity of cultures in each region. The existence of similarities cultural between India and Bali resulted Indian tourist visits Bali increase rapidly from the previous year. The purpose of this research is to find out the factors that influence the decision of Indian tourists to visit Bali. This research was dig by using 150 respondents, the sample in this research used purposive sampling method. Data was collected through a questionnaire distributed to Indian tourists who traveled to Bali, then analyzed by using factor analysis then the data processed by the SPSS version 17.0 program. The result of this research revealed that pull factor formed by service quality factors with eigen value 6.500, relaxation factor with eigen value 2.158, family factor with eigen value 1.789, nature factor with eigen value 1.342 and push factor that formed by social interaction factor with eigen value 1.116. Dominant factor that influencing the decision of Indian tourists to visit Bali is VFR factor (Visiting Friends and relatives) with eigen value of 6,500.